Penyuluhan Literasi Digital Internet Sehat Bagi Pelajar SMA Negeri 1 Kahayan Tengah - Widiatry, Widiatry; Pranatawijaya, Viktor Handrianus; Putra, Putu Bagus Adidyana Anugrah; Sari, Nova Noor Kamala; Christian, Efrans; Priskila, Ressa; Geges, Septian; Kristianti, Novera; Leonardo, Tomas (Fakultas Teknik Universitas Palangka Raya, 2024)
According to the Center for Indonesian Policy Studies children are the most vulnerable group in Indonesia's digital space at risk of exposure to negative content, making them an important target demographic. Therefore, it is important for students to have good digital literacy. The purpose of this activity is to increase the knowledge and understanding of SMA Negeri 1 Kahayan Tengah students about digital literacy, as well as equip them with skills to use the internet safely and responsibly. The targets of this activity are students of SMA Negeri 1 Kahayan Tengah. The activity was carried out using lecture and discussion methods. By participating in this digital literacy counseling, it is hoped that the students of SMA Negeri 1 Kahayan Tengah can increase their knowledge and understanding of digital literacy, so that they can use the internet safely and responsibly, and can contribute optimally to nation building.